Examining the Rules of Taqiyyah and Nafy-e Sabil in Iran's International Relations for the Advancement of New Energy Sources - Fahimeh Fazl Zarandy; abdollah omidifard (پژوهش‌های فقهی مسائل مستحدثه)
Received: 2023 May 7  |   Recieved in revised form: 2021 Jul 4   |   Accepted: 2023 Aug 23   |   Published: 2023 Oct 23The scope of international relations has been a topic of diverse interpretations. It is possible to trace the origins of international regulations and laws back to the post-World War era. The emergence of Islamic Sharia law, particularly the laws derived from the Quran, in Saudi Arabia during the late 6th century had a profound impact on global civilization. Presently, with Shiites having a robust state, scholars and experts in jurisprudence and law bear the responsibility of establishing appropriate relations with other countries while upholding the dignity of Islam and Muslims. This research focuses on the jurisprudential rules of Taqiyyah (religious dissimulation) and Nafy-e Sabil (negation of subordination), separately analyzing their implications for political relations. The aim is to promote the interests of Iran and explore avenues for accessing new energy sources in accordance with the fatwās (jurisprudential decrees) of contemporary jurists. Furthermore, the research examines how to maintain the best interests (maslahat) and dignity of Muslims by adhering to the rule of Nafy-e Sabil and practicing diplomatic Taqiyyah in relations with countries such as China and Russia, which hold significant international political standing. Additionally, it delves into the contemporary discussion surrounding nuclear jurisprudence, considering Nafy-e Sabil and the views of Iran’s leader regarding nuclear energy. The article employs a descriptive-analytical method supported by library resources.  Fazal Zarandi, F. & Omidifard, A. (2023) Examining the Rules of Taqiyyah and Nafy-e Sabil in Iran's International Relations for the Advancement of New Energy Sources. Quarterly of New Perspectives in Islamic Jurisprudence, 1 (1) 205-236. Doi: https://doi.org/10.22091/RCJL.2023.9113.1018 .